Fergus Lamont - Jenkins R. Robin (Edinburgh, Canongate Classics, 1990)
From his origins as an illegitimate child in the slums of Glasgow, Fergus Lamont sets out to reclaim his inheritance and to remake his identity as soldier, poet and would-be aristocrat. Spanning the turn of the century to World War II, Fergus finally hopes to find redemption in a love affair.